The labeling on the "yerba mate" (ilex paraguariensis) packages in the Mercosur" (south american common market) - Sniechowski, Virginia I. (2021)
Fil: Sniechowski, Virginia I. Universidad Nacional de Misiones. Facultad de Ciencias Económicas; Argentina.